Molecular imaging of oxidized collagen quantifies pulmonary and hepatic fibrogenesis - Chen, Howard H. (JCI Insight, 2017)
Fibrosis results from the dysregulation of tissue repair mechanisms affecting major organ systems, leading to chronic extracellular matrix buildup, and progressive, often fatal, organ failure. Current diagnosis relies on invasive biopsies. Noninvasive methods today cannot distinguish actively progressive fibrogenesis from stable scar, and thus are insensitive for monitoring disease activity or therapeutic responses. Collagen oxidation is a universal signature of active fibrogenesis that precedes collagen crosslinking. Biochemically targeting oxidized lysine residues formed by the action of lysyl oxidase on collagen with a small-molecule gadolinium chelate enables targeted molecular magnetic resonance imaging. This noninvasive direct biochemical elucidation of the fibrotic microenvironment specifically and robustly detected and staged pulmonary and hepatic fibrosis progression, and monitored therapeutic response in animal models. Furthermore, this paradigm is translatable and generally applicable to diverse fibroproliferative disorders.